Small-Molecule Inhibitors Targeting Sterol 14 alpha-Demethylase (CYP51): Synthesis, Molecular Modelling and Evaluation AgainstCandida albicans - TATAR, ESRA (WILEY-V C H VERLAG GMBH, 2020)
Fungal infections are a global issue affecting over 150 million people worldwide annually, with 750 000 of these caused by invasiveCandidainfections. Azole drugs are the frontline treatment against fungal infections; however, resistance to current azole antifungals inC. albicansposes a threat to public health. Two series of novel azole derivatives, short and extended derivatives, have been designed, synthesised and investigated for CYP51 inhibitory activity, binding affinity and minimum inhibitory concentration (MIC) againstC. albicansstrains. The short derivatives were more potent against theC. albicansstrains (e. g., MIC 2-(4-chlorophenyl)-N-(2,4-dichlorobenzyl)-3-(1H-imidazol-1-yl)propanamide (5 f) <0.03 mu g/mL,N-(4-((4-chlorophenyl)sulfonamido)benzyl)-2-phenyl-3-(1H-1,2,4-triazol-1-yl)propanamide (12 c), 1 mu g/mL, fluconazole 0.125 mu g/mL) but both displayed comparable enzyme binding and inhibition (5 fK(d)62 +/- 17 nM, IC(50)0.46 mu M;12 cK(d)43 +/- 18 nM, IC(50)0.33 mu M, fluconazoleK(d)41 +/- 13 nM, IC(50)0.31 mu M, posaconazoleK(d)43 +/- 11 nM, IC(50)0.2 mu M). The short series had poor selectivity for CaCYP51 over the human homologue, whereas the selectivity of the extended series, for example, compound12 c, was higher (21.5-fold) than posaconazole (4.7-fold) based onK(d)values, although posaconazole was more selective (615-fold) than12 c(461-fold) based on IC(50)values. Based on inhibitory activity and selectivity profile, the extended series are the better of the two series for further development.
Keywords: antifungal agents; azoles; Candida albicans; CYP51; drug design; molecular dynamics; CANDIDA-ALBICANS; AZOLE RESISTANCE; INVASIVE CANDIDIASIS; ANTIFUNGALS; MUTATIONS; VT-1161; POTENT; ERG11